2020
DOI: 10.1111/jeb.13578
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of infection with intracellular Eimeria spp. and pinworms is reduced in hybrid mice compared to parental subspecies

Abstract: Genetic diversity in animal immune systems is usually beneficial. In hybrid recombinants, this is less clear, as the immune system could also be impacted by genetic conflicts. In the European house mouse hybrid zone, the long‐standing impression that hybrid mice are more highly parasitized and less fit than parentals persists despite the findings of recent studies. Working across a novel transect, we assessed infections by intracellular protozoans, Eimeria spp., and infections by extracellular macroparasites, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 78 publications
4
30
0
Order By: Relevance
“…we found in the present study, resistance and tolerance are decoupled, this can be misleading. In our host system, the house mice, for example, it has been shown that hybrids between M. m. domesticus and M. m. musculus are more resistant to parasites (Baird et al, 2012;Balard et al, 2020), including Eimeria, but tolerance could not be measured under natural conditions (Balard et al, 2020). The effect of parasites on host fitness in the evolution of the house mouse hybrid zone is thus still rather ambiguous (Baird & Goüy de Bellocq, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…we found in the present study, resistance and tolerance are decoupled, this can be misleading. In our host system, the house mice, for example, it has been shown that hybrids between M. m. domesticus and M. m. musculus are more resistant to parasites (Baird et al, 2012;Balard et al, 2020), including Eimeria, but tolerance could not be measured under natural conditions (Balard et al, 2020). The effect of parasites on host fitness in the evolution of the house mouse hybrid zone is thus still rather ambiguous (Baird & Goüy de Bellocq, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…If, as we found in the present study, resistance and tolerance are decoupled this can be misleading. In our host system, the house mice, for example, it has been shown that hybrids between M. m. domesticus and M. m. musculus are more resistant to parasites (Baird et al 2012; Balard et al 2020), including Eimeria , but tolerance could not be measured under natural conditions (Balard et al 2020). The effect of parasites on host fitness in the evolution of the house mouse hybrid zone is thus still rather ambiguous (Baird and Goüy de Bellocq 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The parasite isolates belong to both the most prevalent Eimeria species in this area, namely E. ferrisi (isolate Brandenburg64) and E. falciformis (isolate Brandenburg88)(Jarquín-Díaz et al 2019). Isolate Brandenburg64 was isolated in a 92% M. m. domesticus individual (hybrid index (HI) = 0.08: Proportion of M. m. musculus alleles in a set of 14 diagnostic markers, see Balard et al (2020)) and isolate Brandenburg88 in a 80% M. m. domesticus (HI=0.2). Pre-patency and the peak day of parasite shedding for these isolates were estimated during infection in NMRI laboratory mice (Al-khlifeh et al 2019) which were also used for serial passaging of the isolates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations